Metoclopramide increased cell proliferation in HepG2 cell line and sorafenib attenuated the effect (Annals of Medical Research, 2021)
Aim: Metoclopramide is an antiemetic drug used for treating postoperative or chemotherapy-induced emesis. Sorafenib is a kinase inhibitor drug and is approved for the treatment of advanced primary liver cancer, renal cell carcinoma, thyroid cancer, and acute myeloid leukemia. Hepatocellular cancer is a common cause of cancer-related death and its treatment may require coadministration of an antiemetic medication. The study aims to investigate the effect of metoclopramide on hepatocellular cancer cell proliferation alone or in combination with sorafenib. Material and Methods: Metoclopramide doses of 0.17 µM to 25 µM alone or in combination with sorafenib were administered to human hepatocellular cancer cell line, HepG2. Cell viability and proliferation test was used to determine the possible effects on proliferation. Hematoxylin and Eosin staining was performed to visualize the morphological effects of the treatments.Results: Metoclopramide doses of 0.58 µM, 25µM increased cell proliferation when compared to the control group. Metoclopramide combination groups with 9.9 µM sorafenib were compared with control and sorafenib groups. Each combination group was comparable with the control group. Metoclopramide increased proliferation in certain doses. Safety concerns about its use in hepatocellular cancer should be confirmed in clinical trials Each combination group was comparable with the control group.Conclusion: Metoclopramide increased proliferation in certain doses. Sorafenib inhibited the effect. Safety concerns about its use in hepatocellular cancer should be addressed in clinical trials.
Keywords: Hepatocellular cancer; metoclopramide; pharmacology; sorafenib